KRITIK SENI EKSPRESIONISME PADA KARYA LUKIS AGAPETUS â€œBAIK BOEROEK TANAH AIRKOE JOEGAâ€ - Rahma, Elvira Putri Syuhra Nazilatur; Astawan, I Kadek Yudi (Fakultas Ilmu Budaya, Universitas Brawijaya, 2023)
Expressionism Art Criticism on Agapetusâ€™ Painting â€œBaik Boeroek Tanah Airkoe Joegaâ€. Agapetus is an artist withÂ aÂ surrealist visual concept whose focus is on animals as the subject matter. Agapetus talks a lot about the social condition of society through the representation of animals. This research wants to explore the meaning contained in the work